The fatty acid oxidation product 15‐A3t‐Isoprostane is a potent inhibitor of NFκB transcription and macrophage transformation - Brooks, Joshua D.; Musiek, Erik S.; Koestner, Tyler R.; Stankowski, Jeannette N.; Howard, Jocelyn R.; Brunoldi, Enrico M.; Porta, Alessio; Zanoni, Giuseppe; Vidari, Giovanni; Morrow, Jason D.; Milne, Ginger L.; McLaughlin, BethAnn (Journal of neurochemistry, 2011)
J. Neurochem. (2011) 119, 604–616. Fatty acids such as eicosapentaenoic acid (EPA) have been shown to be beneficial for neurological function and human health. It is widely thought that oxidation products of EPA are responsible for biological activity, although the specific EPA peroxidation product(s) which exert these responses have not yet been identified. In this work we provide the first evidence that the synthesized representative cyclopentenone IsoP, 15‐A3t‐IsoP, serves as a potent inhibitor of lipopolysaccharide‐stimulated macrophage activation. The anti‐inflammatory activities of 15‐A3t‐IsoP were observed in response not only to lipopolysaccharide, but also to tumor necrosis factor alpha and IL‐1b stimulation. Subsequently, this response blocked the ability of these compounds to stimulate nuclear factor kappa b (NFκB) activation and production of proinflammatory cytokines. The bioactivity of 15‐A3t‐IsoP was shown to be dependent upon an unsaturated carbonyl residue which transiently adducts to free thiols. Site directed mutagenesis of the redox sensitive C179 site of the Ikappa kinase beta subunit, blocked the biological activity of 15‐A3t‐IsoP and NFκB activation. The vasoprotective potential of 15‐A3t‐IsoP was underscored by the ability of this compound to block oxidized lipid accumulation, a critical step in foam cell transformation and atherosclerotic plaque formation. Taken together, these are the first data identifying the biological activity of a specific product of EPA peroxidation, which is formed in abundance in vivo. The clear mechanism linking 15‐A3t‐IsoP to redox control of NFκB transcription, and the compound’s ability to block foam cell transformation suggest that 15‐A3t‐IsoP provides a unique and potent tool to provide vaso‐ and cytoprotection under conditions of oxidative stress.